2014
DOI: 10.1371/journal.pone.0087980
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Preferentially Expressed by Highly Virulent Piscine Streptococcus agalactiae upon Interaction with Macrophages

Abstract: Streptococcus agalactiae, long recognized as a mammalian pathogen, is an emerging concern with regard to fish. In this study, we used a mouse model and in vitro cell infection to evaluate the pathogenetic characteristics of S. agalactiae GD201008-001, isolated from tilapia in China. This bacterium was found to be highly virulent and capable of inducing brain damage by migrating into the brain by crossing the blood–brain barrier (BBB). The phagocytosis assays indicated that this bacterium could be internalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
(73 reference statements)
1
15
0
Order By: Relevance
“…The ability to sense the environment and mount an appropriate adaptive transcriptional response may be of crucial importance for S. agalactiae colonization and pathogenicity. Our previous study showed that the expression of hylB was upregulated by the interaction of S. agalactiae with murine macrophages (14). The present study demonstrated that inactivation of hylB reduced the numbers of intracellular viable S. agalactiae cells (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The ability to sense the environment and mount an appropriate adaptive transcriptional response may be of crucial importance for S. agalactiae colonization and pathogenicity. Our previous study showed that the expression of hylB was upregulated by the interaction of S. agalactiae with murine macrophages (14). The present study demonstrated that inactivation of hylB reduced the numbers of intracellular viable S. agalactiae cells (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Female BALB/c mice (5 to 7 weeks of age) were purchased from the Experimental Animal Center, Yangzhou University. Previous studies had shown that the bacterial strain GD201008-001 was highly virulent to BALB/c mice by intraperitoneal administration, with LD 50 values of less than 10 CFU (14). The mice infected with a predetermined dose of 5 ϫ 10 2 CFU (50-fold greater than the LD 50 in mice infected with the GD201008-001 wild-type strain) of the wild-type, mutant, and complemented strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial transcripts were then separated from host cDNA by SCOTS as described previously (Guo et al, 2014). Briefly, denatured, biotinylated, and sonicated A. hydrophila genomic DNA (gDNA) fragments (0.6 μg) were mixed with 5 μg of sonicated ribosomal DNA (from plasmid pMD18-T16S, pMD18-T23S1, and pMD18-T23S2) to pre-block rRNA encoding regions on the gDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Group B Streptococcus (GBS), Streptococcus agalactiae, can colonize the human vaginal and rectal mucosa as a commensal organism (1-3) but can also cause a range of invasive infections in immunocompromised and older adults (4)(5)(6). GBS is also a broad-host-range pathogen capable of causing severe sepsis and meningoencephalitis in fish (7)(8)(9)(10)(11)(12), bovine mastitis (13)(14)(15), and human neonatal sepsis and meningitis (16)(17)(18)(19)(20)(21) and has been recently implicated in chorioamniosis (22,23), causing premature birth (24,25) and stillbirth (25,26). The current strategy to prevent GBS infection of neonates is intrapartum antibiotic prophylaxis (IAP) (27), i.e., intravenous antibiotics given to a woman during labor and delivery.…”
mentioning
confidence: 99%